A strengthened East Asian Summer Monsoon during Pliocene warmth: Evidence from 'red clay' sediments at Pianguan, northern China. (15th April 2018) - Yang, Shiling; Ding, Zhongli; Feng, Shaohua; Jiang, Wenying; Huang, Xiaofang; Guo, Licheng
Graphical abstract: Highlights: Magnetite is the dominant remanence carrier in the 'red clay' sequence at Pianguan. Paleomagnetic data suggest an age range of 6.9–2.9 Ma for the Pianguan 'red clay'. The summer monsoon rainbelt shifted northward in East Asia during Pliocene warmth. Abstract: The Pliocene epoch (5.3–2.6 Ma) is the most recent geological interval in which atmospheric CO2 levels were similar to those of the present day (∼400 ppmv). This epoch is therefore considered to be the best ancient analog for predicting a future anthropogenic greenhouse world. In order to determine the response of the East Asian Summer Monsoon (EASM) rainbelt during Pliocene warmth, a 71.9 m-thick aeolian 'red clay' sequence at Pianguan was investigated. Rock magnetic experiments suggest that magnetite of pseudo-single domain size is the dominant remanence carrier in the 'red clay' sequence. Magnetostratigraphic data, constrained by lithostratigraphy, show that the polarity zones of the 'red clay' section correlate with those between subchrons C2An.2r and C3An.2n of the geomagnetic polarity time scale (GPTS), yielding an age range of 6.9–2.9 Ma. The 'red clay' deposits exhibit enhanced weathering intensity over two time intervals, namely 5.23–4.3 Ma and 3.7–2.9 Ma, as evidenced by their well-developed pedogenic characteristics, as well as their high free to total Fe2 O3 ratios and high redness (a ∗ ) values, which in turn indicate an increased summer monsoon intensity during most of the Pliocene. Furthermore, the pedogenic characteristics of the well-weathered Pliocene soils were compared with those of paleosol unit S5 (one of the best-developed soil units found in Pleistocene loess) from the Yulin, Luochuan and Lantian sections, which constitute a north-south transect across the Chinese Loess Plateau (CLP). The Pliocene soils at Pianguan show a pedogenic development similar to the S5 (∼0.5 Ma) at Luochuan in the central Plateau, which is located some 3.7° latitude south of Pianguan, but this development is much stronger than that observed at Yulin in the north, and weaker than that seen at Lantian in the south. This may imply a more northerly penetration (∼400 km) of the monsoon rainbelt during Pliocene warmth compared with the Pleistocene interglacial period (∼0.5 Ma ago), supporting the prediction that the EASM rainbelt shifts northward in a warmer world. In addition, our results show that Pliocene warmth was unlikely to have been characterized by a permanent El Niño-like state, but was possibly influenced by a La Niña-like state.